Case Report: Intestinal Obstruction in a Patient on Antiplatelet Therapy (International Journal of Advanced Medical Sciences and Technology (IJAMST), 2025)
Background Antiplatelet therapy is commonly prescribed for various cardiovascular conditions, but it represents a unique challenge in dealing with surgical emergencies, such as intestinal obstruction. Our case is a 47-year-old patient who had a history of CABG and was on maintenance dual antiplatelet therapy, "Aspirin and Clopidogrel", attended the ER with a short history of acute abdominal pain associated with vomiting and distension. Clinical findings and imaging studiesrevealed features of intestinal obstruction.